(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
A cross sectional prospective study was carried out to determine the prevalence of demographic status associated with pet owners and animals, and pattern of drugs used in prescription during study period from February 2019 to April 2019 at Central Veterinary Hospital (CVH), Dhaka, Bangladesh. A total of 493 clinical cases were analyzed and found that educated and illiterate calculated as 64.2% and 13.8% of dog owners, and 89.4% and 10.6% of cat owners. Among the pet animals, males were higher (dogs 64.3%, cats 52.1%) compared to females (dogs 35.7%, cats 47.9%). In relation to breed of pet animals, local breed was higher in both cases of dogs (33.4%) and cats (55.9%). Tendency of pet owners for deworming (36.4% in dogs, 23.9% in cat) and vaccination (45.3% in dogs, 37.8% in cats) were not satisfactory. The prevalence of noninfectious diseases was 40.7% in dogs and 59.6% in cats followed by infectious diseases (26.6% in dogs, 14.9% in cats). Overall prescribed antimicrobials were higher (49.5% in dogs, 62.2% in cat) than others. Among them, most frequently used antimicrobials in dogs were fluroquinolone with metronidazole/beta lactams (93.7%) in infectious case followed by Cephalosporin (56.3%) due to non-infectious case. On the contrary, metronidazole was used (100%) due to noninfectious case followed by cephalosporin (28.3%) in infectious case in cats. These results indicate the level of awareness of vaccination and deworming practice, management styles of their pets in Dhaka and socio economic condition of owners. Vol. 9, No. 3, December 2022: 299-306